Fatima Mernissi’s Thoughts About Women’s Leadership - sadiyah, Fatichatul; Luthfiyanto , Muhammad; Bighas , Khadijah A; Firmansyah (The Islamic Education and Multiculturalism Foundation, 2024)
In this paper, the author will discuss the thoughts of Fatima Mernissi in criticizing the hadis on women’s leadership. From the results of her investigation, Mernissi criticized Abu Bakrah in relation to the narration of the hadis as follows: 1) Abu Bakrah is difficult to trace his lineage because he was originally a slave who was freed when he joined the Muslims. 2) Abu Bakrah was sentenced to qazaf, because he could not prove the charge of zina against al-Mughirah ibn Syu’bah at the time of the Caliph Umar bin al-Khattab. 3) Looking at the historical context, why did Abu Bakrah remember this hadis (which, if correctly uttered by the Prophet, means that he has passed a period of approximately 25 years) after knowing Aisha had lost the war, while the initial stance he took was neutral. Based on this rule, Mernissi concluded that Abu Bakrah was a narrator who was rejected, and his hadis was not acceptable. Based on the foregoing reasons, Mernissi concluded that even though the hadis was contained in Sahih al-Bukhari, it was still debated by the jurists. According to her, this hadis is used as an argument to displace women in the decision-making process.